Performance and Performativity – How to Discuss Presence - Fischer-Lichte, Erika (Aesthetica Preprint, 2025)
Today’s aesthetics discourse sees presence as a specific aesthetic quality not just of the human body but of objects from our environment, including products of technical and electronic media (in terms of their “presence effects”). I will apply the term “presence” to the performer’s body and subsequently examine whether, within the frame of the aesthetics of the performative, it can be meaningfully related to objects from our environment.